Exploring proteins within the coccolith matrix - Craig J. Dedman; Nishant Chauhan; Alba González-Lanchas; Chloë Baldreki; Adam A. Dowle; Tony R. Larson; Renee B. Y. Lee; Rosalind E. M. Rickaby (Scientific Reports)
Abstract Coccolithophores comprise a major component of the oceanic carbon cycle. These unicellular algae produce ornate structures made of calcium carbonate, termed coccoliths, representing ~ 50% of calcite production in the open ocean. The exact molecular mechanisms which direct and control coccolith formation are unknown. In this study, we report on the presence and functional features of proteins within the coccoliths produced by a range of model coccolithophore species including: the globally abundant and well-studied Gephyrocapsa huxleyi (formerly Emiliania huxleyi) and related Gephyrocapsa oceanica, as well as the larger and more heavily calcified Coccolithus braarudii. Protein features were compared between species and against biomineralisation proteins previously identified in other marine calcifying organisms. Notably, several protein features were consistently seen across the examined coccolithophore species, including the cell signalling 14-3-3 domain, chromosome segregation SMC ATPase domain, as well as proteins involved in protein processing and protease inhibition. The copper-binding cupredoxin domain was observed in both Gephyrocapsa species, as well as other marine calcifiers, suggestive of a requirement of Cu in biomineralisation. Building consensus with existing work, we highlight the pentapeptide repeat as a feature which is associated with the coccolith matrix, being identified in all three examined species, and propose that this structural motif may play a role in controlling coccolith growth. This preliminary study provides insight towards the functional diversity of calcification machinery in coccolithophores and presents a number of candidates for future research towards understanding the biochemical controls which direct coccolithogenesis.